Playful gamification teaching strategy for the development of gross motor coordination in children aged 4 to 5 years - Rodriguez Veliz, Cecilia Johana; Zambrano Acosta, Jimmy Manuel; Chica Chica, Leonardo Fabricio (Universidad Ciencia y Tecnología, 2024)
The educational strategy of playful gamification is a tool that contributes significantly to the development of motor coordination of boys and girls, allowing them to improve the process of acquiring skills and abilities and making learning much more effective, playful, and didactic. Where the direct beneficiaries are the children. The methodology used is specified in the use of a mixed type approach (qualitative and quantitative) with a descriptive type with the use of theoretical, inductive-deductive, and empirical methods, the instruments of the interview with teachers and the observation sheet for boys and girls, relevant results are specified that are based on the application of the instruments where it is indicated that the development of children’s gross motor coordination becomes much more significant with the integration of a didactic strategy of playful gamification.